Implementation of seamless care in a hospital: A qualitative study focused on clinical pharmacists - PEVEC, TEODOR; REPEC, SABINA (Anali PAZU, 2024)
In Slovenia, the notion of seamless care has been relatively new in the recent past. It suggests that clinical pharmacists have a significant role in working closely with patients and enhancing their safety. The perspective of clinical pharmacists in a novel work environment piqued our curiosity. We conducted a qualitative research. We obtained the necessary information through interviews conducted with four clinical pharmacists who have the most theoretical and practical knowledge in the field of seamless care. The interviewees believe that the implementation of seamless care in clinical practice is important and positive. However, they are distracted by administrative obstacles in carrying out seamless care. The detection of clinical pharmacists is appropriate and enables the development of the method to other professional groups.